Penggunaan Model Pembelajaran Project Based Learning Untuk Meningkatkan Keterampilan Membaca Siswa di Kelas III SD GMIM 24 Manembo-Nembo - Mangumpisan, Sri Wati; Paus, Juldus R.; Mandey, Steven (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out how to use the Project Based Learning Model to Improve the Reading Skills of Class III students at SD GMIM 24 Manembo-nembo. Researchers used a classroom action research design (PTK) according to Kemmis and Mc. Taggart (Zainal Aqaib, 2006: 31) includes four stages, namely: (1) planning, (2) action, (3) observation, and (4) reflection which is carried out in two cycles. The subjects of this research were class III students at SD GMIM 24 Manembo-nembo using the Project Based Learning learning model. Data collection techniques were carried out through observation and tests, namely by directly observing the implementation of learning actions and written tests to determine the extent to which students were able to understand the material from the two cycles. The data analysis technique uses the . formula. The results obtained in cycle I reached 37.03%, while in cycle II student learning outcomes reached 100%. Students understood and were able to achieve the expected learning objectives. Based on the results of the research and discussion, it can be concluded that teachers at GMIM 24 Manembo-nembo Elementary School are expected to apply the Project Based Learning learning model to improve students' reading skills in class III at GMIM 24 Manembo-nembo Elementary School.